Competition strategies during writing in a second language: age and levels of complexity - Figueiredo, Sandra (2019)
(1) Background: Research in second language (L2) writing in the European context is an emerging tendency in L2 studies. European countries have become new hosts to immigrants in very recent years and new applied research is needed to aid schools in their inclusion process. (2) Method: This study examined differences in writing performance by comparing 99 immigrant students in Portugal between 7 and 17 years of age. They were assessed in six distinct aspects by means of a written essay in order to perceive how maturity and language groups impact competencies such as lexicon, grammar, sociolinguistics and use of strategies. (3) Results: The results were examined according to the competition model of MacWhinney and Bates (1989; MacWhinney 2005) and concluded that older students wrote more proﬁcient essays. First language (L1) and parallel instruction in L1 were examined as covariates against their effects. (4) Discussion: Students who received parallel instruction in their L1 had better results in L2 writing, but only age-produced signiﬁcant differences will be discussed.